2021
DOI: 10.5222/tmcd.2021.72687
|View full text |Cite
|
Sign up to set email alerts
|

Çeşitli Klinik Örneklerden İzole Edilen Staphylococcus aureus Suşlarının Antibiyotik Direnç Oranları

Abstract: Objective: Staphylococcus aureus is an important pathogen that can cause both community and hospital-acquired infections. The presence of methicillin resistant isolates limits treatment options. The aim of this study was to determine the antibiotic resistance rates in S. aureus strains isolated from outpatients and inpatients in our hospital. Method: Various clinical specimens were evaluated retrospectively between 2016-2019 and S. aureus strains were included in the study. Bacterial identification and antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
3
0
4
Order By: Relevance
“…In this present investigation, 50.0% Gr negative bacteria isolated from St1 were resistant to ceftazidime, cefotaxime, clindamycin, and ampicillin, whereas only %25 of the isolates from St2 showed clindamycin and cefotaxime resistance. Although the prevalence of ARB in many freshwater sources of Turkey has been previously reported (Ozgumus et al 2009;Akkan et al 2011), this is the first study that indicated the high frequency of ampicillin and clindamycin resistance in surface waters of Kilis. Buyukkaya Kayıs (2022) noted that E. coli isolated from 5 different stations in Ataturk Dam in Adıyaman was resistant to chloramphenicol, and tetracycline antibiotics contrary to our findings.…”
Section: Resultsmentioning
confidence: 78%
“…In this present investigation, 50.0% Gr negative bacteria isolated from St1 were resistant to ceftazidime, cefotaxime, clindamycin, and ampicillin, whereas only %25 of the isolates from St2 showed clindamycin and cefotaxime resistance. Although the prevalence of ARB in many freshwater sources of Turkey has been previously reported (Ozgumus et al 2009;Akkan et al 2011), this is the first study that indicated the high frequency of ampicillin and clindamycin resistance in surface waters of Kilis. Buyukkaya Kayıs (2022) noted that E. coli isolated from 5 different stations in Ataturk Dam in Adıyaman was resistant to chloramphenicol, and tetracycline antibiotics contrary to our findings.…”
Section: Resultsmentioning
confidence: 78%
“…A. baumannii can be found in nature and in human skin flora or may be isolated from clinical specimens [7][8]. Resistance to antibiotics used in infections caused by these strains has become a significant global health problem, as increasing multi-antibiotic resistance reduces the possibility of treatment [9,10]. Many Acinetobacter species have shown resistance to antibiotics such as quinolones, carbapenems, and cephalosporins.…”
Section: Introductionmentioning
confidence: 99%
“…Mevcut direnç oranlarıyla TMP-SMX bölgemizde sistit tedavisinde ampirik tedavi için uygun bir ajan haline gelmiştir. Ülkemizde E. coli'ye karşı florokinolon direnci %7-41 arasında değişmektedir (11,(14)(15)(16)(17)(18). Bizim çalışmamızda bu oran %20.73 olup Türkiye geneliyle benzerdir.…”
Section: Introductionunclassified